Penerapan Metode Pembelajaran Picture And Picture Unuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Ilmu Pengetahuan Sosial ( IPS ) Di SDN 01 Rantau Selatan - PEBRIANA SARI; Suryatik; Ismi Yulizar; Muhammad Zulham Munthe (Cendekia Madani Nusantara, 2024)
This research aims to determine student learning outcomes and student activities in participating in classroom learning using the Picture and Picture method. This research is classroom action research (PTK) which was carried out in two cycles with the research subjects being class III students, totaling 30 students. Observational data collection techniques. The research results obtained on student learning outcomes, the percentage of students who were classically active in cycle I was 40%. then in cycle II the percentage of classically active student learning activities was 87%. From the results of the research and discussion, it can be concluded that the learning process using the Picture and Picture learning method can improve the learning outcomes of class III students at SDN 01 Rantau Selatan, Rantau Selatan District, Labuhanbatu Regency. This is proven by the increase in the number of students who achieved the KKM, cycle I by 23% and cycle II by 87%. This success was due to the application of the Picture and Picture method by instilling basic concepts by guiding students to be better able to recognize social conditions in the environment. they. By using the Picture and Picture method, students' attitudes are more active in the teaching and learning process, able to pay attention to the learning process well, able to ask questions to the teacher if they are not well understood, this is indicated by a good learning process, so it can be said that by using the observation sheet students can It is known that the increase in student learning outcomes from pre-research to cycle II can be said to be going well. This proves that the next cycle is not necessary. Therefore, using the picture and picture method has been proven to improve learning outcomes in social studies lessons for class III students at SDN 01 Rantau Selatan.